Development and Evaluation of an English Speaking Skills Web-based Resource: A Pilot Study - Izzati Md Fuad, Nurul; Mohd Shah, Parilah; Mohamad, Maslawati (International Journal of Engineering and Technology, 2018)
This study aimed to develop and evaluate a web-based resource known as â€˜Hey Letâ€™s Speakâ€™. The resource provides assistance for secondary school students in Malaysian suburban and rural areas. â€˜Hey Letâ€™s Speakâ€™ was developed using the design and development research method (DDR) to establish a suitable design for the respondents and involved collaborative effort among the researcher, teachers and experts in the field. The respondents chosen were intermediate and weak secondary school ESL learners from the Terengganu state. The web-based resource is evaluated using both Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) to measure respondentsâ€™ acceptance and use of the web-based resource. Preliminary results suggest that the ESL learners responded positively towards the web-based resource usefulness, ease of use, ease of learning and satisfaction. The findings based on UTAUT also show positive results with expert expectancy, attitude towards using technology, social influence and facilitating conditions. The findings provide some insights on the benefits of web-based learning to the ESL pupils; thus, educators will be able to use the web-based resource effectively and more frequently in speaking skills lessons. Â Â